Application of Behavioral Architecture in The Land Arrangement of a Simple Rental Flat, Bong Cino Tomb Area, Madiun City - Rifo Ibnu Falah; Firdha Ayu Atika; Failasuf Herman Hendra (Faculty of Civil Engeneering and Planning - ITATS, 2023)
The city of Madiun is currently experiencing an increase in population with various backgrounds. Based on the description of the problem, a long-term plan is needed to anticipate the population's need for housing. There is a problem that is in the spotlight, namely residents who build homes on the slum land of the Bong Cino Cemetery area and have occupied the area for tens of years with the nature of activities that are contrary to the norm. In the problems that have been described, it is necessary to plan and design flats for residents in the Bong Cino Cemetery area by applying a behavioral architectural theme to be able to communicate with users through sensing the buildings that affect human psychology. The types of research conducted are field studies and literature studies. In collecting data using interview methods, observation methods, documentary methods, and literature methods as well as the types and sources of data used are primary data and secondary data. From the discussion of the problems, it can be concluded that designing the low-cost flat building, namely focusing on land management by applying the concept of macro-defensible space which is applied to land planning, produces a role in the mechanism of action prevention for environmental protection and is expected to be of assistance and benefit to the community and to be able to overcome problems in the Bong Cino Tomb area.